Problem of personality in psychosomatic medicine - Kočiūnas, R. (Psichologija, 1983)
The problem of participation of personality traits in rising of psychosomatic diseases is reviewed. Two aspects of the problem are discussed: the possible existence of specific premorbid personality structure in patients with different psychosomatic diseases (within the framework of psychological specificity concept) and personality traits common to many psychosomatic patients (alexithymic personality). It is concluded that only complex investigation of the aforesaid aspects may help to determine the role of personality factor in rising and course of psychosomatic diseases.